Smart Transfer Certificate Generator and Employer Verification Using Blockchain - Modi, Shabina Sayyad; Shingate, Rashmi Kishor; Jagtap, Rutuja Girish; Kadam, Mayuri Dattatray; Sabale, Rutuja Hemant (International Journal of Computer Sciences and Engineering, 2023)
Around 315 million students are enrolled in universities in India, which has the world`s largest body. There are an enormous number of students who graduate each year with different degrees. In their education, they require various certificates, transcripts, degrees, diplomas, transfer certificates, etc., Due to the high number of graduate students, it can be difficult to establish whether an academic document is legitimate, and without any validating authority, it becomes even more challenging. To address this, we suggest using blockchain technology to create digital transfer certificates that are tamper-proof and will serve as a reliable form of authentication both in academic institutions and workplaces. Also, it will help the institute Tracking of these certificates and their verification manually becomes a hectic job and also the process will be handy for the students. Through the unique QR code of each document, certain authorities can easily verify the documents.